Cosmic Rays' study with a TRASGO detector - García Castro, Damián
TRASGOs are a new generation of cosmic ray detectors to study the influence of the Earth’s magnetic field and the atmosphere on the cosmic ray flux. This thesis presents the calibration, reconstruction, and analysis algorithms developed for two TRASGOs: TRISTAN and TRAGALDABAS. TRISTAN performed a series of unprecedented latitudinal surveys before being installed in Antarctica at the Spanish Antarctic Base JCI, and TRAGALDABAS is located in Santiago de Compostela. We have investigated the effects of the barometric pressure, atmospheric temperature, and cutoff rigidity on the cosmic ray data as well as the correlation with space weather events. 2023-07-22